AN ANALYSIS OF EDUCATIONAL VALUE BY SCOOT DERRICKSON IN THE DOCTOR STRANGE MOVIE - umri, mili; Triyogo, agus; syaprizal (LP3MKIL, 2021)
This research study aimed to analyze of Educational Value by Scoot Derrickson in the Doctor Strange Movie. This study would answer the question “What are the educational values in Doctor Strange Movie ?”, by answering that question the researcher will know what were the educational values found in the Doctor Strange Movie. In this study the method used to found the educational values was qualitative descriptive method. The researcher found some educational values in the movie that divided into two parts, there are Values of being and values of giving. Values of being were: honesty, courage, peace ability, self-discipline, confidence and capability. Values of giving were: loyalty, respect, love, unselfishness, sensitivity, kindness, friendliness, justice and mercy.